2022
DOI: 10.52965/001c.37310
|View full text |Cite
|
Sign up to set email alerts
|

Age over 50 does not predict results in anterior cruciate ligament reconstruction.

Abstract: Introduction Grown in the worldwide population of over 50 of age individuals who remain in good health and continue to engage in sports has led to an increase of anterior cruciate ligament (ACL) tears in this aged population. ACL reconstruction was reserved for young and active athletes, but seems to produce good outcomes also in over 50s. Purpose To compare the patient-reported functional scores, arthrometric outcomes, and complications of primary ACL reconstruction between older (>50 years) and younger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 40 , 41 , 42 Corona et al. 43 showed comparable results with younger patients at a large systematic review. Weng et al.…”
Section: Discussionmentioning
confidence: 88%
“… 40 , 41 , 42 Corona et al. 43 showed comparable results with younger patients at a large systematic review. Weng et al.…”
Section: Discussionmentioning
confidence: 88%
“…Medial meniscus ramp tears have detrimental effects on overall knee stability and if left untreated, can contribute to the early progression of osteoarthritis [9]. Biomechanical studies have reported that concomitant ACL and medial meniscus ramp tears increase anterior tibial translation and internal rotation of the knee compared to an isolated ACL tear state [1,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…ACLR is also increasing in middle-aged patients, and it has been seen that ACLR may be performed without concern for inferior clinical and arthrometric results compared with younger patients (<50 years) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%